TINJAUAN YURIDIS MENGENAI BATASAN ANTARA PERBUATAN MALADMINISTRASI DENGAN TINDAK PIDANA KORUPSI - Odie Faiz Guslan (STIH Putri Maharaja, 2018)
The aim of this resecearch is to determine about the limitations between the act of goverment officials (bestuurhandelingen) that inflict state financial loss qualified as a maladministration or a corruption offence. The research method used is Juridical Normative. The result of the study show that, not every act of goverment officials that inflict state financial loss qualified as a corruption offence. In determine of the limits between maladministration act and corruption offence, the government officials must avoid itself from acts of discretion that containing the nuances of criminal law such as: cheating (deceit), manipulation, mispresentation, concealment of facts, breach of trust, subterfuge, or illegal circumvention.